Synthesis, characterization, and photoelectric properties of iridium(iii) complexes containing an N hetero-dibenzofuran C^N ligand. Issue 18 (17th March 2021) - Ma, Zequn; Jing, Chaojun; Hang, Deyu; Fan, Hongtao; Duan, Lumeng; Fang, Shuqing; Yan, Li
Abstract : Three high-efficient green light iridium complexes were designed and prepared. Thermal stabilities, electrochemical properties, electroluminescence performances and substituents effects are presented and discussed in this study. Abstract : In this study, three high-efficient green light iridium(iii ) complexes were designed and synthesized, wherein 2-methyl-8-(2-pyridine) benzofuran [2, 3- B ] pyridine (MPBFP) is the main ligand and three β-diketone derivatives, namely 3, 7-diethyl-4, 6-nondiazone (detd), 2, 2, 6, 6-tetramethyl-3, 5-heptyldione (tmd) and acetylacetone (acac), are ancillary ligands. The thermal stabilities, electrochemical properties, and electroluminescence (EL) performance of these three complexes, namely (MPBFP)2 Ir(detd), (MPBFP)2 Ir(tmd) and (MPBFP)2 Ir(acac), were investigated. The results show that the absorption peaks of the three complexes range from 260 to 340 nm, and the maximum emission wavelengths are 537 nm, 544 nm and 540 nm, respectively. The LUMO level is −2.18 eV, −2.20 eV, −2.21 eV, and the HOMO level is −5.30 eV, −5.25 eV, and −5.25 eV, respectively. The thermal decomposition temperatures of each of the three compounds are 359 °C, 389 °C and 410 °C respectively, with a weight loss of 5%. Green phosphorescent electroluminescent devices were prepared with the structure of ITO/HAT-CN/TAPC/TCTA/TCTA:X/Bepp2/LiF/Al, and the three complexes were dispersed in the organic light-emitting layer as the guest material X. The maximum external quantum efficiency of the devices is 17.2%, 16.7%, and 16.5%, respectively. The maximum brightness is 57 328 cd m −2, 69 267 cd m −2 and 69 267 cd m −2, respectively. With respect to the EL properties, (MPBFP)2 Ir(detd) is the best performer among the three complexes. The different performances exhibited by these complexes were discussed from the view point of substituent effect on the β-diketone ligands.